A systematic review and meta-analysis of the efficacy and safety of arbidol in the treatment of coronavirus disease 2019. Issue 30 (24th July 2020) - Wang, Xuemei; Xie, Ping; Sun, Guojuan; Zhao, Min; Deng, Zhumei; Zhou, Yunxia; Bao, Shuting
Abstract: Background: Coronavirus disease 2019 (COVID-19) is highly contagious, and the epidemic has spread to hundreds of countries around the world, and seriously threatens the life safety of people around the world. Arbidol is an antiviral drug with high potential against COVID-19, but evidence of effectiveness and safety is lacking. The systematic review protocol aims to formulate a research plan that can evaluate the efficacy and safety of arbidol for COVID-19. Methods: The retrieval time will be from the database establishment to June 2020. The retrieval database will include the Cochrane Library, PubMed, Embase, OVID, CNKI, Wanfang, VIP, CBM, etc. The primary outcome will be clinical efficacy, and the secondary results will be accompanying symptoms, time for the temperature to return to normal, time of novel coronavirus nucleic acid turning negative, blood sample test, Computed Tomography examination, length of hospitalization, adverse reactions, and adverse events. RevManV.5.3 software will be used for meta-analysis, and fixed effects model, random-effects model, subgroup analysis, and descriptive analysis will be adopted according to the heterogeneity of the research results. Results: To provide the latest evidence of clinical efficacy and safety of arbidol in the treatment of COVID-19. Conclusion: Our study will provide the latest evidence analysis of the efficacy and safety of arbidol for COVID-19, to provide evidence-based medicine for the prevention and control of this epidemic. Registration details: PROSPERO CRD42020189203.